(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2021)
The arrival of sound films from World films to Karakalpakfilm. Analysis of creative work on sound operators and their films. The impact of uzbekfilm on the film Karakalpakfilm.